Looking Through the Gender Lens: Women in Sabah Under APPGM-SDG Solution Projects - Hasan, Muhammad Rahimi; Abd Rahman, Muhamad Azwan; Eko Prayitno Joko (Journal of Technical Education and Training, 2023)
In Sabah, five solution projects under the auspices of All-Party Parliamentary Group Malaysia on Sustainable Development Goals (APPGM-SDG) were related to the ‘Goal 5 Achieve gender equality and empower all women and girls. One of the main aspects evaluated towards solution providers and beneficiaries is ‘gender dimension’. Hence, this article underlines three research objectives. Firstly, to identify gender-driven issues faced by the women in their community. Secondly, to demonstrate the strategies executed by solution providers in collaboration with beneficiaries’ groups. Thirdly, to analyze the impacts of the solution projects by utilizing four aspects: (i) deep (personal), (ii) clear (skills), (iii) wide (network), and (iv) high (system) as a measuring tool. In terms of research methodology, this study utilizes qualitative approach in data collection and analysis comprised of (i) observation, (ii) focus group discussion (FGD), and (iii) document analysis. Based on the analysis, three main findings were obtained in line with the objectives of this study. Firstly, main issues were based on local community experiences in education, household economy and health. Despite that, most of the issues require a national and global solution framework for the betterment of their community. Secondly, good synergy between solution providers (expertise and networks) and beneficiaries’ groups (local wisdom and motivation) is ‘the key to successes for solution projects. Thirdly, assessment on four aspects of this study shows the beneficiaries groups have been empowered through knowledge, skills, and networks. The most significant findings are that the beneficiaries’ groups established a system—as a registered and licensed groups on their own and as a part of the larger groups to ensure their sustainability—thus, ensuring ‘leave no woman behind’.